Pullout performance of modified threads in glass fiber reinforced plastic (GFRP) composites - Karaca, Faruk (Carl Hanser Verlag, 2017)
Glass fiber reinforced plastic (GFRP) composite materials are widely used in novel industries. They are generally used in electrical environments due to their high thermal strength and mechanical resistance under present conditions with lower weight. In most of the applications, the GFRP is subjected to screwing for assembling. In this study, the pull-out strength performance of the screw was investigated in view of thread modification. In order to determine the optimum thread minor diameter, several pullout tests were performed. Therefore, the modified values showed significantly a better performance than standard values. This novel design was compared with numerical analyses in ANSYS and it was observed that numerical results had a good agreement with experimental results.
Keywords: Glass Fiber reinforced plastic (GFRP); pullout strength; thread modification; stripping load; ANSYS